Improved efficiency and cost reduction in the emergency department by replacing contemporary sensitive with high-sensitivity cardiac troponin immunoassay - Aloe, Rosalia; Lippi, Giuseppe; Di Pietro, Martina; Bonfanti, Laura; Dipalo, Mariella; Comelli, Ivan; Avanzini, Paola; Sanchis-Gomar, Fabian; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2019)
Background: Although unquestionable evidence has been provided that high-sensitive (HS) cardiac troponin (cTn) immunoassay outperform the former contemporary-sensitive techniques, some clinicians are still hesitant to implement HS methods in routine clinical practice. This study was hence planned to evaluate the impact of replacing a contemporary-sensitive with HS cTnI immunoassay on hospital and laboratory workload. Methods: Information on the total number of cTnI tests ordered, total number of blood samples collected, total number of CK-MB tests ordered, number of patients with the first HS-cTnI value below the limit of detection (LoD) and cumulative HS-cTnI values was extracted from the local hospital information system for the semesters before and after the HS method was introduced. Results: Although the total emergency department (ED) visits modestly increased after introducing HS-cTnI, the number of total cTnI tests declined by over 10%. A substantial reduction of single-sample test requests was noted, accompanied by a considerable decline of 3- and 4-sample collections (i.e., -61% and -73%, respectively). A high percentage of patients (27.5%) displayed HS-cTnI values <LoD at admission, thus allowing safe discharge. The introduction of HS cTnI immunoassay was effective to collapse the number of CK-MB test requested and also generated favorable return of investment for the part of laboratory budget concerning cTnI testing (-3.2% of total costs for cTnI and -99.8% of total costs for CK-MB). Conclusion: The results of this study show substantial organizational and economic benefits by replacing contemporary-sensitive with HS cTnI immunoassays. (www.actabiomedica.it)